(3GdQSGdI GdLGeYI PGJ GdahGFO GdfGaYI JGL QSGFd GNhGf GdUaGs
(3ChdgG (B:s
(3GYde CjgG GdCN GdHGQ GdQMje GjOc Gddg hEjGfG HQhM efg hGYGffG s
(3BNQgG (B:s
(3hEdjge efbGOhf hdGeQge JGHYhf s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3edi edc (B_ (3EjQGf (B(5439) s
Keywords: (3GdadSaI hGdefWbs